Seismic Analysis of Low-Rise Self-Centering Prestressed Concrete Frames considering Soil-Structure Interaction - Liang-Long Song; Tong Guo; Xin Shi (Shock and Vibration)
In this study, the seismic behavior of low-rise self-centering (SC) prestressed concrete frames considering soil-structure interaction (SSI) is presented. For this purpose, a typical 4-story SC concrete frame, with and without flexible foundations, is analyzed through nonlinear dynamic analysis. Ground motion sets with two hazard levels are selected for analysis. A conventional reinforced concrete (RC) frame is also studied, and the structural demands of the RC and SC frames are compared in terms of peak and residual drifts, base shear, residual settlement, and rotation of foundation. The analysis results show that considering soil-structure interaction generally increases the peak and residual drift demands and reduces the base shear and connection rotation demands when compared to fixed base conditions. For the cases with and without flexible foundations, the SC frame is found to have comparable peak story drifts with the RC frame and have the inherent potential of significantly reducing the residual drifts. The seismic analysis results of the frames with flexible bases show that the RC and SC frames can experience foundation damage due to excessive residual foundation rotations after the maximum considered earthquake (MCE).